The Utilization of Hygrometer and Exhaust with IoT Technology in Temperature Control in Maggot (BSF) Containers: Temperature Control Innovation in BSF Maggot Cultivation through Hygrometer and Exhaust IoT Technology - Ramadhan, Alvin Rizki; Azzahra, Trisya Puteri; Maharani, Kristina; Rimantho, Dino (P3M Politeknik Perkapalan Negeri Surabaya, 2025)
Black Soldier Fly (BSF) maggot is an important organism in animal feed and organic waste decomposition due to its high nutritional content and its ability to decompose up to 56% of organic waste mass. This research aims to design an Internet of Things (IoT)-based Biopond to optimize temperature and humidity, in order to increase maggot productivity. The designed biopond uses thick plastic material, equipped with temperature and humidity sensors and an automatic Exhaust Fan integrated with IoT technology. The Quality Function Deployment (QFD) method was used to design the system based on the needs of farmers, with data collected through questionnaires and related literature. The results showed that the IoT-based biopond was significantly more efficient in decomposing waste and supporting maggot growth with temperatures maintained between 28°C - 31°C and optimal humidity. The system increased maggot biomass and waste decomposition efficiency, showing great potential for wider application in organic waste management.